e-Infrastructure Acceptance in e-Health, eLearning and e-Agriculture in Zimbabwe: The Quest for the User Acceptance Variable - Chiome, Chrispen (My University, 2013)
One of the best ways to achieve global literacy is through communication, collaborative learning, research, and problem solving. Technology helps tremendously in these areas, so it is a great tool to use in this process. As e-infrastructures gain ground in many African countries and at the same time promises a new way of delivering health, education and agriculture. New technologies should be readily acceptable in order to deliver these essential services to the populace. However, against a background of previous studies pointing to e-learning as a monster under the bed (Chiome, Kurasha and Mupa, 2011) and after 98% of the students failed to voluntarily register for an e-learning blended programme, this research set out to find the factors affecting user acceptance of e- infrastructures in health, agriculture and education. This was a survey of institutions engaged in e-agriculture, e-health and e-learning in Zimbabwe. A purposive sample of 65students who were exposed to e-infrastructures was interviewed in order to determine the user acceptance variable applicable in Zimbabwe. The study found out that e-infrastructure users made rational choices faced with alternatives, belief in the usefulness or lack of it of the system, too much effort put into using technology, content richness, e-infrastructure usefulness and update regularity of the e-infrastructure are some of the absolutely vital technology acceptance variables. The research argues that the ability to navigate the complex life and work environments in the globally competitive information age requires e-infrastructure developers to pay rigorous attention to technology acceptance to engage e-infrastructure users other than the “early adopters” with the opportunities in e-infrastructures.
Keywords: e-infrastructure; e-learning; e-agriculture; e-health; technology adoption; new technologies